Etyczne i polityczno-prawne dylematy samorządu terytorialnego w Polsce - Kasiński, Michał (Annales. Etyka w Życiu Gospodarczym, 2009)
The reform of Polish self-government in the 90's has led to the restoration of local democracy. However, the self-governmental institutions soon fell into crisis, having nearly lost the social trust required for the realisation of their mission. The principal cause behind this phenomenon was the atrophy of moral, political and legal responsibility of the local authorities towards the communities that have elected them. There is a twofold source of weaknesses and dangers for Polish self-government: the erroneous way of introducing changes in the system of government, and the forthcoming sociopolitical phenomena that hampered or even made it impossible to achieve some of the goals of the reform. We support the radical revision of legal regulation to remove these weaknesses. The basis for such a change will be the principle of subsidiarity as a governing rule for the entire system of public authority. This will ensure that the communities of inhabitants are seen as primary subjects of self-governmental power, and their power is rooted in citizens' rights to self-government. It is also necessary to ensure a truly pluralistic character of territorial power. Thus the citizens and their associations will have an influence on the election and functioning of the selfgovernmental bodies. The Author warns against the risk of emergence of a class of local and regional 'mandarins' in Polish public life – a class of practically ineradicable and systematically deficient leadership, likely to emerge should the mechanisms of democratic responsibility fail to be restored into the governmental bodies. The article ends with suggestions of particular legal changes aiming at the correct formation of Polish self-governmental institutions in both morally and socially rightful sense.